PROMOTING GLOBAL CULTURAL AWARENESS THROUGH SUPPLEMENTARY MATERIALS FOR PRIMARY INDONESIAN EFL STUDENTS - Dewi, Helda Krisyana; Utami, I.G.A. Lokita Purnamika; Santosa, Made Hery (STKIP Citra Bakti, 2025)
This research aimed to explore the development process and evaluate the quality of English supplementary materials integrated with global culture. This study followed a developmental research approach guided by Branch (2009), which consists of five key stages: Analysis, Design, Development, Implementation, and Evaluation. The participants of this study consisted of 25 fifth-grade students and an English teacher. A total of 25 students and one teacher were purposefully selected using a purposive sampling technique. To gather comprehensive data, the study employed a combination of content analysis, interviews, and surveys. The development of the English supplementary materials integrated with global culture for fifth-grade students followed a multi-step process from designing a blueprint outlining topics, learning objectives, and activities that combined English skills with global knowledge, cultural behaviors, and artifacts. The materials were created using Canva to produce a colorful, engaging layout with visual elements and a friendly character named Squirrel as a guide. The content was adapted from the fifth-grade primary English textbook, My Next Words, and enriched with global cultural elements. The developed English supplementary materials integrated with global culture were effectively implemented in the classroom and received positive feedback from students, teachers, and experts. The user and expert judgments further confirmed the quality of the materials, with an average rating of 4.36, classifying them as “good” in terms of relevance, design, and global culture integration. These results indicate that the developed supplementary materials are effective, engaging, and beneficial in supporting students’ English learning and cultural awareness in the classroom setting